Basic theology - Ryrie, Charles Caldwell, 1925- (Wheaton, IL Victor, 1986)
Includes bibliographical references and indexes.
Portions of this book were taken from: What you should know about the rapture. -- Moody, c.1981; The Holy Spirit. -- Moody, c. 1965; What you should know about inerrancy. -- Moody, c. 1981; The final countdown. -- Victor, c.1982
Keywords: Doctrine (theology).